The first microsolvation step for furans: New experiments and benchmarking strategies - Gottschalk, Hannes C.; Poblotzki, Anja; Fatima, Mariyam; Obenchain, Daniel A.; Pérez, Cristóbal; Antony, Jens; Auer, Alexander A.; Baptista, Leonardo; Benoit, David M.; Bistoni, Giovanni; Bohle, Fabian; Dahmani, Rahma; et al. (The journal of chemical physics, 2020)
The site-specific first microsolvation step of furan and some of its derivatives with methanol is explored to benchmark the ability of quantum-chemical methods to describe the structure, energetics, and vibrational spectrum at low temperature. Infrared and microwave spectra in supersonic jet expansions are used to quantify the docking preference and some relevant quantum states of the model complexes. Microwave spectroscopy strictly rules out in-plane docking of methanol as opposed to the top coordination of the aromatic ring. Contrasting comparison strategies, which emphasize either the experimental or the theoretical input, are explored. Within the harmonic approximation, only a few composite computational approaches are able to achieve a satisfactory performance. Deuteration experiments suggest that the harmonic treatment itself is largely justified for the zero-point energy, likely and by design due to the systematic cancellation of important anharmonic contributions between the docking variants. Therefore, discrepancies between experiment and theory for the isomer abundance are tentatively assigned to electronic structure deficiencies, but uncertainties remain on the nuclear dynamics side. Attempts to include anharmonic contributions indicate that for systems of this size, a uniform treatment of anharmonicity with systematically improved performance is not yet in sight.
Gesehen am 02.07.2020